Feasibility study on the production of peanut milk - Abis, Ma. Remedios O.; Nadera, Nita G.; Navarro, Ma. Gliceria T. (Quezon City College of Engineering, 1987)
Plant design: Peanut milk -- Process: wet extraction method -- Capacity: 11 metric tons per day -- Plant location: Barrio Pantubigan, San Rafael, Bulacan -- Total land area: 4,000 sq.m. -- Pay-out period: 1.79 years -- Annual rate of return: 55.92% -- Product composition (weight percentage): Crude peanut milk 93.9%, sugar 5.9%, NaCMC 0.2% -- Product color: Milky white to white -- Product package size: 250 ml. and 1000 ml. plastic bottles -- Raw materials: peanuts -- By-products: Peanut skins used as fuel, Filter cake used as feed meal -- Operation: 8 hrs/day (2 shifts), 360 days/year
Submitted in partial fulfillment of the requirements in ChE 62
Keywords: Factories -- Design and construction; Peanut products